Effectiveness of a multimedia resource in histopathology practical teaching in medical undergraduates-a comparative study - Dr. Subitha. K; Dr. Lillykutty Pothen; Dr. Sajith Kumar R.; Mr. M. Kandamuthan; Dr. Usha Poothiode (Tropical Journal of Pathology and Microbiology, 1970)
Introduction: Computer technology is found to be a valuable tool to add to the medical teacher’s tool kit. This study was done to assess whether learning through digitalized images have advantage over conventional methods in learning histopathology practical.Method: Digital images of another set of 20 slides and specimens were taken and were made into a CD. From a total number of 30 students, 15 students were randomly selected by lot method and they were the study group and the rest 15 students were the control group. Total of 20 slides and specimens were taught in 5 classes over a period of one month. The control group students attended 5 classes where they were taught by conventional methods. The study group, in addition to teaching by conventional method was shown the CD pictures. Assessment was done for both groups as a post test in the form of a spotter exam which included 10 slides and 10 specimens.Result: Mean improvement by the newer method was found to be 18.6 with a standard deviation of 23.3 and this improvement was statistically significant as t=2.87 and p value <.01.The mean score obtained by the students by conventional method was 53 % whereas the mean score obtained by the students by the newer method was 67 %.Discussion: The incorporation of digital images in teaching histopathology practical’s combined with the conventional method of teaching showed a statistically significant change in learning.